Identifying Determinants for Traveled Distance and Bypassing in Outpatient Care: A Scoping Review - Nicole Zander MSc; Jessica Dukart BSc; Neeltje van den Berg PhD; Jobst Augustin PhD (SAGE Publishing, 2019)
The outpatient sector represents a growing share of health care. This review examines how patients choose their physician for continuous outpatient care and why they are willing to bypass the nearest physician. It was conducted according to the PRISMA extension for scoping reviews (PRISMA-ScR). Three databases (PubMed/Medline, ScienceDirect, and Ovid Medline) were searched, focusing on articles in which distance influenced the choice of physician. In all, 1,308 articles were accessed, and 17 selected for final review. First, we extracted methods for assessing distance traveled and bypassing. Second, we identified determinants that directly influence the traveled distance and transferred all into a conceptual framework. The center of this framework is the individual "willingness-to-go", which reflects the willingness of patients to accept additional distances. Our findings can support studies on patient mobility and physician choice, which are essential for examining both the distribution and use of medical services, as well as for adequate need related planning.